Cancer Stem Cells in Moderately Differentiated Buccal Mucosal Squamous Cell Carcinoma Express Components of the Renin–Angiotensin System - Featherston, Therese; Yu, Helen H.; Dunne, Jonathan C.; Chibnall, Alice M.; Brasch, Helen D.; Davis, Paul F.; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2016)
Aim We have recently identified and characterized cancer stem cell (CSC) subpopulations within moderately differentiated buccal mucosal squamous cell carcinoma (MDBMSCC). We hypothesized that these CSCs express components of the renin-angiotensin system (RAS). Methods 3,3-Diaminobenzidine (DAB) immunohistochemical (IHC) staining was performed on formalin-fixed paraffin-embedded MDBMSCC samples to investigate the expression of the components of the RAS: pro(renin) receptor (PRR), angiotensin converting enzyme (ACE), angiotensin II receptor 1 (ATIIR1) and angiotensin II receptor 2 (ATIIR2). NanoString mRNA gene expression analysis and Western Blotting (WB) were performed on snap-frozen MDBMSCC samples to confirm gene expression and translation of these transcripts, respectively. Double immunofluorescent (IF) IHC staining of these components of the RAS with the embryonic stem cell markers OCT4 or SALL4 was performed to demonstrate their localization in relation to the CSC subpopulations within MDBMSCC. Results DAB IHC staining demonstrated expression of PRR, ACE, ATIIR1 and ATIIR2 in MDBMSCC. IF IHC staining showed that PRR was expressed by the CSC subpopulations within the tumor nests, the peri-tumoral stroma and the endothelium of the microvessels within the peri-tumoral stroma. ATIIR1 and ATIIR2 were localized to the CSC subpopulations within the tumor nests and the peri-tumoral stroma, while ACE was localized to the endothelium of the microvessels within the peri-tumoral stroma. WB and NanoString analyses confirmed protein expression and transcription activation of PRR, ACE and ATIIR1 but not of ATIIR2, respectively.